Islamic Model of Children's Spiritual Education (CSE); its influence on improvement of communicational behaviour with non-coreligionists - Ganjvar, Mahdi (International journal of children's spirituality, 2019)
This paper aims at showing the efficiency and influence of spiritual education on improvement of communicational behaviour of children with the followers of others religions through presentation of an Islamic model derived from Quran and prophetic tradition. In the first part of the paper, we have provided a conceptual analysis of spirituality along with a short history of the attention to spiritual education of children in the world. Then, we introduce the Islamic model of spirituality and its moral foundations and aspects. In the final part of the paper, we have inferred the key factors of Islamic Model for Children's Spiritual Education that play a vital role in the reinforcement of communicational skills of the children with the non-coreligionists. The method used in the current research is of descriptive-analytic type.